Quantitative planning and decision-making techniques (with particular reference to agricultural applications) - Harrison, Harold (Statistical and Social Inquiry Society of Ireland, 1969)
It is intended in this paper to describe the application of (i) Mathematical Programming, and (ii) Markov Cham Theory to some of the problems in agriculture, industry and economics with which the Operational Research scientist is faced today.
Read before the Society, 11 November 1968
Keywords: Quantitative planning; Mathematical programming; Agriculture; Markov chain theory; 314.15